The Multisensory Book Design: A Learning Medium for Dyslexic Children Reading the Qur'an Through Reflection on Concrete Objects - Susanti, Cela Petty; Maulaya, Rosendah Dwi; Siswanto, Maisya Himatuz Zakiyya; Qolbi, Safira Naurin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
A dyslexic child experiences a common obstacle in the learning process due to having difficulty reading and recognizing letters (corrective and remedial readers). If left unchecked, the potential of dyslexic children will be hampered because reading is a basic human ability. Therefore, in this study, researchers designed a learning media design that makes it easier for dyslexic children to recognize hijaiyah letters. The research method used is R&D using the ADDIE development model. The study that the researchers conducted was limited to the development of design, so the purpose of this study was to provide an overview of the design of multisensory mirror book media. The design is developed with a printed book-based that will maximize the function of the senses of sight and touch. Dyslexic children will be invited to learn while playing by reflecting hijaiyah letters on concrete objects found in everyday life. In their learning, they were also invited to play by attaching glitter to hijaiyah stickers and then touching them. His motor function was tested by rewriting hijaiyah letters and then checking the correctness of the writing using a mirror. In the future, the design developed by researchers can continue to be refined to help dyslexic children learn hijaiyah letters to make it easier and more fun.